PENERAPAN GOOGLE CLASSROOM UNTUK PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS X C MULTIMEDIA SMKN 03 KOTA BATU - Devi Alfina Anggraeni; Illyas Thohari; Ika Anggraheni (VICRATINA, 2020)
2020 is the hard year for education. There is a virus that threatening the people. The virus named Covid-19, it’s found in China and spread almost all over the world. And now Kota Wisata Batu is in red zone, it’s showed by the number of people get infected is 42 people. To breakin the covid-19 chain, Indonesians minister of education and culture ask the institution in red, orange, yellow zone in Indonesia to use e-learning for the way to deliver the lesson to their students. Using observation, interview and documentation for data collection procedure this research aims is the assignment method can make it easy for the students for learn from home or not. And it aims to describe the plans, the Implementation and the effectiveness of the result of the Assignment method using Google Classroom at grade 10th C Multimedia SMKN 03 Kota Batu. And from this research show that assignment method using Google Classroom is not effective because there’s any problem during using Google Classroom make 6 students submit their assignment exceed the deadlines.